Evolution of nanohillocks by fullerene ion-induced localized plasma - Altuijri, R.; El Maati, L. Abu; Ahmad, M.; Alharthi, N. S.; Moslem, W. M.; Elkamash, I. S. (Frontiers in Physics, 2023)
Since surface nanostructures etch without chemicals, their development is a crucial tech- nical process. Surface nanohillocks may be created by irradiating yttrium iron garnet (YIG) with 30 MeV C60 cluster ions. The nanohillock creation mechanism is disputed. In this study, we propose that the formation mechanism is a plasma collective effect of charged particles that depends on localized rogue waves. Rogue waves will explain YIG surface nanohillock cre- ation using a traditional hydrodynamic plasma model. Analytically solving hydrodynamic ion fluid equations and Maxwellian electron distributions yields a nonlinear Schr¨odinger equation. Solving the latter gives us plausible rogue wave domains. Rogue waves concentrate charged ions from the surroundings into a small, confined zone, generating surface nanohillocks. The relevance of different plasma parameters is highlighted in the rogue wave profile.